TQM constructs development and validation a survey of selected Philippine companies - Talavera, Ma. Gloria V.; Zamora, Elvira A. (Quezon City College of Business Administration, University of the Philippines Diliman, 2000)
This study was conducted to determine the critical components of a Total Quality management program (referered to as TQM constructs) and the specific strategies, policies and programs that should comprise each TQM construct (referred to as TQM elements); to validate these TQM constructs in selected companies in the Philippines; and to utilize this validated instrument in assessing their extent of TQM adoptaion and in evaluating the possible association of the respondent firms' performance with the extent of TQM adoption. Two satges of data gathering were conducted for this purpose. Survey 1 aimed to determine the managers' perception on to the critical elements that should compromise a particular TQM construct. The 2nd survey sought to determine the extent to which these critical TQM elements are being implemented. Development of the TQM constructs involved the theoretical derivation of the TQM construct from literature. Validation of the instrument dealth with assessing its reliability through the Internal Consistency Method with Cronbach coefficient alpha as the relevant coefficient to evaluate. Content validity was done through panel review while the construct validity was determined through both Exploratory and Confirmatory Factor Analyses. Determinaion of the factors affecting extent of TQM adoption and the association of performance with TQM adoption was evaluated through Multiple Linear Regression (MLR) analysis. The interrelationships of the TQM constructs and their possible association with quality performance was determined through Structural Equation Modeling using PROC CALIS (Covariance Structure Analysis). Results from Survery 1 indicate that majority of the elements included in the 72-item instrument were generally perceived important by 347 managers form 63 companies. TQM elements rated not critical belong to the following TQM constructs - Supplier Quality Management, Customer Orientation, Human Resources Management and Benchmarking. On the other hand, based on a total of 64 respondent firms in Survey 2 representing 323 managers, about 60 percent of the firms exhibited large extent of TQM adoption with the other 40 percent having moderate extent of adoption. The TQM elements rated not critical were generally the same elements moderately implemented. The discrepancy in the perception of importance and extent of practice of the TQM constructs and elements may be due to resource constraints associated with TQM adoption. Reliability tests show significantly high Cronbach coefficient alpha for the whole instrument and for each TQM cosntruct indicating the high reliability of the instrument. The analysis of the construct validity using Common Factor Analysis, with perception of importance as basis for scale development, shows the convergence of certain elements of a construct with another construct where it shares similarity in function performed. The resulting groupings were found to be relevant, conceptually meaningful and presented the multidimensional aspect of TQM implementation. A significant difference in the extent of TQM Adoption and performance was noted for respondent firms categorized according to industry affiliation, ownership structure, export orientation and quality management grid classification. Results of the MLR analysis reveals firm size (measured in terms of asset level) and technology level (represented by Flexible Manufacturing System) as significant determinants of the extent of TQM adoption. These findings support the notion that to implement TQM successfully, provision of top management commitment in terms of time and resources are critical. It was observed that TQM adoption was found to have a significant association with quality, business and organizational performance. About six to 12 percent of the improvement in quality performance (measured in terms of improvement in relative product quality and reduction in defects rate) was found to be associated with TQM adoption. Similarly, approximately five to 11 percent improvement in business performance, as measured by net profits and sales, may be attributed to TQM. On the other hand, improvements in majority of the organizational performance parameters were found to be highly associated (20-30 percent) with TQM indicating the critical role played by TQM in motivating employees. Results of the Structural Equation Modelling show the retention of four TQM factors having significant association with quality performance (as measured by relative product quality.) These factors include (1) getting feedback in the design of quality management strategies, (2) employee involvement, (3) quality management technique orientation, and (4) quality monitoring and control. The elements associated with these factors reflect the interplay of both technique and philosophy orientations of quality management system in affecting quality performance. Top management commitmment no longer emerged as a separate construct but its elements were subsumed in the four factors inidcating that in practice top management's commitment should be present in every component of its quality management program.
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Total quality management -- Philippines; Manufacturing industries -- Management. -- Philippines; Industrial management -- Philippines